Handbook of research on military, aeronautical, and maritime logistics and operations - Ochoa Ortiz Zezzatti, Carlos Alberto (Advances in logistics, operations, and management science (ALOMS) book series, 2016)
This book compiles interdisciplinary research on diverse issues related to logistics from an inclusive range of methodological perspectives offering theoretical, experimental research, and case studies on logistics strategies and operations management with an emphasis on military, aeronautical, and maritime environments.